Das Andere der „erdumspannenden Gesellschaft“ - Torsten Hahn (Recherches Germaniques)
The future vision described in the 1924 novel Berge Meere und Giganten begins with the global spread of a social formation that strives to export its technology and security system to even the most remote regions. There is some opposition, however: the novel presents a multitude of actors who resist planetary homogenization and integration into networks (e.g., of global transport). In this context, I explore the construction of alterity or radical otherness. The most spectacular among these actors is the desert, which becomes a pole of resistance against Western norms. The paper traces the inter- and pre-texts that result in the construction of an ‘other space’, i.e. contemporary geopolitical and geobiographical literature.